Molecular adaptations of adipose tissue to 6 weeks of morning fasting vs. daily breakfast consumption in lean and obese adults - Gonzalez, Javier T.; Richardson, Judith D.; Chowdhury, Enhad A.; Koumanov, Francoise; Holman, Geoffrey D.; Cooper, Scott; Thompson, Dylan; Tsintzas, Kostas; Betts, James A. (Wiley, 2018)
This study assessed molecular responses of human subcutaneous abdominal adipose tissue (SCAT) to 6 weeks of morning fasting. Forty‐nine healthy lean (n = 29) and obese (n = 20) adults provided SCAT biopsies before and after 6 weeks of morning fasting (FAST; 0 kcal until 12.00 h) or daily breakfast consumption (BFAST; ≥700 kcal before 11.00 h). Biopsies were analysed for mRNA levels of selected genes, and GLUT4 and Akt protein content. Basal and insulin‐stimulated Akt activation and tissue glucose uptake rates were also determined. In lean individuals, lipid turnover and insulin signalling genes (ACADM and IRS2) were up‐regulated with FAST versus BFAST (ACADM: 1.14 (95% CI: 0.97–1.30) versus 0.80 (95% CI: 0.64–0.96), P = 0.007; IRS2: 1.75 (95% CI: 1.33–2.16) versus 1.09 (95% CI: 0.67–1.51), P = 0.03, respectively). In obese individuals, no differential (FAST versus BFAST) expression was observed in genes involved in lipid turnover (all P > 0.1). GLUT4, Akt protein content and insulin‐stimulated Akt phosphorylation were unaffected by FAST versus BFAST in both lean and obese cohorts (all P > 0.1). Lower insulin‐stimulated glucose uptake rates in obese versus lean individuals were eradicated when normalised to whole‐body fat mass (P = 0.416). We conclude that morning fasting up‐regulates lipid turnover genes in SCAT of lean individuals. Secondly, altered SCAT insulin sensitivity with morning fasting is unlikely to be explained by signalling proximal to Akt. Finally, lower insulin‐stimulated SCAT glucose uptake rates in obese individuals are proportional to whole‐body fat mass, suggesting a compensatory down‐regulation, presumably to prevent excessive de novo lipogenesis in adipose tissue. This trial was registered as ISRCTN31521726.